MDMX inhibits casein kinase 1α activity and stimulates Wnt signaling - Huang, Qingling (EMBO J, 2020)
Casein kinase 1 alpha (CK1α) is a serine/threonine kinase with numerous functions, including regulating the Wnt/β‐catenin and p53 pathways. CK1α has a well‐established role in inhibiting the p53 tumor suppressor by binding to MDMX and stimulating MDMX‐p53 interaction. MDMX purified from cells contains near‐stoichiometric amounts of CK1α, suggesting that MDMX may in turn regulate CK1α function. We present evidence that MDMX is a potent competitive inhibitor of CK1α kinase activity (K (i) = 8 nM). Depletion of MDMX increases CK1α activity and β‐catenin S45 phosphorylation, whereas ectopic MDMX expression inhibits CK1α activity and β‐catenin phosphorylation. The MDMX acidic domain and zinc finger are necessary and sufficient for binding and inhibition of CK1α. P53 binding to MDMX disrupts an intramolecular auto‐regulatory interaction and enhances its ability to inhibit CK1α. P53‐null mice expressing the MDMX(W) (200S/W201G) mutant, defective in CK1α binding, exhibit reduced Wnt/β‐catenin target gene expression and delayed tumor development. Therefore, MDMX is a physiological inhibitor of CK1α and has a role in modulating cellular response to Wnt signaling. The MDMX‐CK1α interaction may account for certain p53‐independent functions of MDMX.